2016
DOI: 10.1007/s00464-016-4965-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bag extraction to prevent wound infection on umbilical port site wound on elective laparoscopic cholecystectomy: a prospective randomised clinical trial

Abstract: The determinant of wound infection in elective laparoscopic cholecystectomy is not the direct contact of the gallbladder with the wound; therefore, bag extraction is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…3 ). Concerning sensitivity analysis the estimated pooled risk ratio ranged from 0.72 to 0.96 omitting Comajuncosas et al [ 17 ] or Majid et al [ 18 ] studies, respectively, both not statistically significant. Harbord test did not reveal the occurrence of small-study effect ( p = 0.892) and the funnel-plot showed no noteworthy pattern (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…3 ). Concerning sensitivity analysis the estimated pooled risk ratio ranged from 0.72 to 0.96 omitting Comajuncosas et al [ 17 ] or Majid et al [ 18 ] studies, respectively, both not statistically significant. Harbord test did not reveal the occurrence of small-study effect ( p = 0.892) and the funnel-plot showed no noteworthy pattern (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The eligible studies were 2 randomized trials [ 16 , 17 ] and a multicenter prospective study [ 18 ]. Harling et al [ 16 ] compared groups receiving a dose of cefuroxime (750 mg i.v.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Present survey revealed that only 43% of surgeons performed gallbladder's extraction through a "bag" protecting extraction device, and 12% does so without a bag, currently there is no clear recommendation regarding the risk of galls stones swarming, surgical wound infection or tumour dissemination in unrecognized gallbladder cancer. 4,11,12 The macroscopic examination of the gallbladder at the end of CH and the sending of the product for an histological study is an absolute necessity, since more than 37% of gallbladder cancers are not suspicious even after examining the inside of the operative part. 13 This notion seems to be acquired by surgeons who participated in this survey, all surgeons carry out a histpathological study, even those who do not have a laboratory in their health structure 64.8% (n=79).…”
Section: Discussionmentioning
confidence: 99%